The corruptor - Halsted, Dan; Foley, James; Halsted, Dan ([Los Angeles, Ca.] : New Line Cinema, 1999)
Nick Chen is one of the NYPD's most decorated officers. The first Chinese-born immigrant on the force, Chen has used his close ties with a group of Chine'businessman' known as the Triads to rise through the ranks. Now, a gold shield detective and the star officer on the city's highly touted Asian Gang Unit; it's Chen's job to keep the peace in Chinatown
Executive producer, Oliver Stone ; writer, Robert Pucci
Cast: Chow Yun Fatt, Mark Wahlberg, Ric Young
VCD format
Keywords: Police films